2018
DOI: 10.21873/anticanres.13077
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression in the Progression and Aggressiveness of Papillary Thyroid Carcinoma

Abstract: In the last two decades microRNAs have received great attention in research because of their ability to regulate gene expression. Many studies have shown that defects in different microRNA molecules are linked to many diseases; however, their contribution towards thyroid disease has not been fully explored. Herein, we present a short review of the present state of knowledge on microRNAs, such as their origin, their biogenesis and biological function, as well as their differential expression in papillary thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 64 publications
2
31
0
Order By: Relevance
“…Numerous studies have demonstrated that various miRNAs are aberrantly expressed in thyroid cancer and play indispensable roles in the malignancy of thyroid cancer (38-40). Almost all aggressive characteristics of thyroid cancer have been demonstrated to be modulated by miRNAs via regulating the expression of their target genes (41). In the past few decades, multiple miRNAs have been extensively studied in thyroid cancer (13,14,42); however, many miRNAs remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that various miRNAs are aberrantly expressed in thyroid cancer and play indispensable roles in the malignancy of thyroid cancer (38-40). Almost all aggressive characteristics of thyroid cancer have been demonstrated to be modulated by miRNAs via regulating the expression of their target genes (41). In the past few decades, multiple miRNAs have been extensively studied in thyroid cancer (13,14,42); however, many miRNAs remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after, He et al showed the up-regulation of miR-221, miR-222, and miR-146 in PTC patients, which are the first dysregulated miRNAs reported in thyroid cancer (49). To date, many additional studies have identified miRNAs involved in thyroid cancer initiation and progression (50,51). Here, we summarize the recent list of dysregulated miRNAs in thyroid cancer, published from 2015 onward, with implications in cancer initiation and progression, briefly listed in Table 1.…”
Section: Mirnas Regulating Thyroid Carcinogenesismentioning
confidence: 99%
“…During PTC pathogenesis, some critical genes (including BRAF, RET, KRAS, and PI3KCA) through mutation or chromosomal translocation continuously activate their dependent downstream signaling pathways, such as mitogen-activated protein kinase (MAPK), phosphoinositide 3-kinase (PI3K)/AKT, nuclear factor-κB (NF-κB), and Notch-1, and thereby lead to cellular proliferation, migration, invasion, and angiogenesis [15][16][17]. Recently, emerging clinical trials and experimental researches also demonstrated that some noncoding RNA expressions, such as miRs-21, -34b, -221/222, lncRNA ATB, lncRNA H19, lncRNA HOXA-AS2, circITCH, and circZFR, showed significant association with aggressive clinicopathologic feature in PTC, including tumor size, lymphovascular invasion, lymph node metastases, and presence of BRAF V600E mutation [17][18][19][20][21]. Despite the advances in tumorigenesis, metastasis, and therapy, the underlying mechanism of PTC remains unclear.…”
Section: Introductionmentioning
confidence: 99%